Analysis of the Recognition, Measurement, Reporting, and Disclosure of Research Costs In Hospitals: A Study at RSIY PDHI Yogyakarta - Anas Tasya; Avininda Dewi Nindiasari (PT Publikasiku Academic Solution, 2026)
Research in hospitals plays an important role in improving the quality of healthcare services and advancing scientific knowledge. However, in practice, the management of research costs still faces various challenges, particularly in the aspects of recognition, measurement, reporting, and disclosure, which are not yet fully standardized. Therefore, this study aims to analyze the implementation of these four aspects in managing research costs in hospitals.This study employed a qualitative method with a descriptive approach. The research was conducted at RSIY PDHI Yogyakarta, focusing on units related to research and financial management. Data were collected through semi-structured interviews and documentation, involving informants who were directly engaged in managing research costs. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and method triangulation. The results indicate that research cost recognition is carried out when transactions or expenditures occur, while costs listed in the Research Budget Plan (RAB) are still considered estimates and are not recognized until they are realized. Cost measurement is conducted using a costing approach, which includes labor costs, equipment usage, consumables, and overhead costs. In terms of reporting, research costs are not presented separately in the financial statements but are combined under education and training (diklat) expense accounts. This condition indicates that the disclosure of research costs has not been carried out separately, resulting in less detailed and less transparent information. In addition, research cost management has not been fully effective, as it still relies on manual recording systems using spreadsheets, which increases the risk of errors and data inconsistencies. Budget changes also frequently occur during the research process due to adjustments to field conditions.Overall, research cost management in hospitals still needs improvement through strengthening accounting information systems, developing more structured guidelines, and separating the reporting and disclosure of research costs to enhance transparency, accountability, and efficiency.